(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The study aimed to provide a theoretical and descriptive presentation of the municipality of Misurata in Libya. The researcher has shown through the research the location of the municipality of Misurata and its borders, as well as an explanation of some of the population centers there. It also aims to identify the trends in the development of population growth and its components of births, deaths, migration and the factors influencing population changes in terms of population growth and the most important reasons for these changes, through an analysis of population data and censuses that were conducted during the study period using the descriptive analytical approach, equations and statistical methods to measure population growth and future expectations and the analysis of population variables. The researcher relied on the available statistics for the population census in that region during the period from 1984 to 2020. The study revealed an increase in the size of the population to reach 245,218 people during thirty-six years, i.e. 6811 / people in year, and the population growth rate will reach 2.5% for the year 2020.